Predicting the Application of Moral Principles Based on HEXACO Personality Traits and Moral Intelligence - Azimi Fashi, Leila; Dehghan, Fatemeh; Bolandpaz, Marzieh; Teymurian Motlagh, Negar (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to predict the application of moral principles—operationalized as moral intelligence—based on HEXACO personality traits among university students.Methods and Materials: A descriptive-correlational design was employed using a sample of 152 students from the Science and Research Branch of Islamic Azad University in Tehran, selected through convenience sampling. Data were collected using two standardized instruments: the Moral Intelligence Scale developed by Lennick and Kiel (2005) and the 60-item HEXACO Personality Inventory created by Ashton and Lee (2000). Data analysis was conducted using SPSS-27 software, incorporating Pearson correlation coefficients and multiple regression analysis to determine the relationships and predictive capacities of the personality traits concerning moral intelligence.Findings: Results showed a statistically significant and positive correlation between moral intelligence and two HEXACO dimensions: Honesty–Humility (r = .20, p < .05) and Extraversion (r = .48, p < .01). Multiple regression analysis revealed that Honesty–Humility (β = .18, p = .025) and Extraversion (β = .45, p = .001) significantly predicted moral intelligence, accounting for 30% of its variance (R² = .30). The other four personality traits—Emotionality, Agreeableness, Conscientiousness, and Openness to Experience—did not show statistically significant relationships with moral intelligence in this sample.Conclusion: The findings underscore the predictive roles of Honesty–Humility and Extraversion in determining moral intelligence among university students. These results suggest that personality-informed strategies may be useful in promoting moral development in academic and developmental settings. The study contributes to the literature linking personality traits to ethical functioning and highlights potential pathways for ethical training and intervention based on personality profiles.